2017
DOI: 10.25304/rlt.v25.1981
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative technologies, higher order thinking and self-sufficient learning: A case study of adult learners

Abstract: The inclusion of online elements in learning environments is becoming commonplace in Post Compulsory Education. A variety of research into the value of such elements is available, and this study aims to add further evidence by looking specifically at the use of collaborative technologies such as online discussion forums and wikis to encourage higher order thinking and self-sufficient learning. In particular, the research examines existing pedagogical models including Salmon's five-stage model, along with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…This sort of learning provides students with the freedom and prospect to advance at their own pace, based on their learning requirements and styles. The outcome concurs with the findings by Fryer and Bovee (2018), Johnson (2017) and Kuo and Belland (2016) which all revealed that blended learning is effective in developing English vocabulary abilities. Hence, it can be surmised that blended learning assisted in the improvement of aircraft maintenance learners' technical terms acquisition and performance.…”
Section: Facilitate Blended Learningsupporting
confidence: 91%
“…This sort of learning provides students with the freedom and prospect to advance at their own pace, based on their learning requirements and styles. The outcome concurs with the findings by Fryer and Bovee (2018), Johnson (2017) and Kuo and Belland (2016) which all revealed that blended learning is effective in developing English vocabulary abilities. Hence, it can be surmised that blended learning assisted in the improvement of aircraft maintenance learners' technical terms acquisition and performance.…”
Section: Facilitate Blended Learningsupporting
confidence: 91%
“…In the context of technology use for online learning, helping organize learners to communicate and cooperate in learning activities with various techniques, tools, and means and enabling them to access and make effective use of these resources to promote knowledge construction are essential ( Lai, 2015 ). Online learning as a technology-facilitated learning should be based on the learning theories and pedagogy that are appropriate to it ( Kop and Fournier, 2011 ), with its effectiveness building largely on how the technology is designed and implemented in teaching and learning ( Johnson, 2017 ; Eynon and Malmberg, 2020 ). Teachers have a big role to play in choosing teaching strategies to ensure the integration of students’ knowledge acquisition and their own learning experience in online environments ( Ertmer and Ottenbreit-Leftwich, 2010 ), and to accelerate the understanding of the basic characteristics of technology to enhance learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of this model during the design process offers appropriate support to online students in each stage as they develop expertise in online learning (Salmon, 2004). Although there has been some critique of the model (Moule, 2007), it has been applied to support the design of online courses in different contexts (Johnson, 2017;Karaman & Orhan Özen, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%